Influence of SARS-CoV-2 variants of concern and maternal vaccination status on neonatal outcome - Rolf Felix Maier; Mario Rüdiger; Nadine Mand; Matthias Hutten; Ulrich Pecks (BMJ Paediatrics Open)
SARS-CoV-2 infection during pregnancy can adversely affect maternal and neonatal health, although risks vary depending on the variant of concern (VOC). Omicron, although highly infectious, causes fewer maternal and neonatal complications than earlier VOC, so vaccination may be considered unnecessary in planned pregnancy. Using data from the CRONOS registry, we compared pregnancy outcomes according to VOC and vaccination status. We found that vaccination during pregnancy reduced preterm birth rates compared with unvaccinated or vaccinated women with Omicron infection, without increasing severe neonatal outcomes. Given the risks associated with preterm birth, the study consistently supports vaccination recommendations for women planning pregnancy.